What is a child? : childhood, psychoanalysis, and discourse - Plastow, Michael Gerard (Karnac, 2015)
Childhood is defined in different preconceived manners by different discourses. Thus the categories defined by age such as infant, child, adolescent and so on, are to some extent arbitrary divisions that are subject to the evolution in clinical, societal, ideological and political discourses. Within psychoanalysis there has been a conflation of childhood construed through the retrospective memories of adults, and childhood as seen through the perspective of infant observations. In What is a Child? Michael Gerard Plastow argues that the place of the child as subject in the fullest sense has bee.